Research on the situation of returning to poverty and governance measures in poverty-alleviated areas in China: A case study of Linxia Hui autonomous prefecture in Gansu Province, China - Min, Song; Regina Garai, Abdullah (Learning Gate, 2024)
Since the 18th National Congress of the Communist Party of China, under the strong leadership of the Party Central Committee with Comrade Xi Jinping at its core, China’s poverty reduction efforts have achieved historic success, with absolute poverty completely eradicated by 2020. However, the long-standing issue of returning to poverty has occasionally occurred, manifesting at different times and in various regions. This study aims to explore the phenomenon of returning to poverty in rural areas under the context of China’s targeted poverty alleviation and its governance measures. Based on this, Linxia Hui Autonomous Prefecture in Gansu Province, China (hereinafter referred to as “Linxia Prefecture”) is selected as the research area. Through a combination of data analysis and field interviews, the study examines the situation and historical trends of returning to poverty in Linxia Prefecture in recent years, ultimately summarizing the current measures to prevent and control returning to poverty in the region. The results indicate that the phenomenon of returning to poverty in Linxia Prefecture exhibits significant annual and regional differences at the county and township levels, with diverse causes and changing primary factors of returning to poverty. At the household level, low education levels, a small number of labor force, low quality of labor, and poor overall health of households are the main internal factors contributing to the return to poverty among those who have previously been lifted out of poverty.